An Indigenous American Conceptualization of Substance Abuse and Its Treatment. Issue 2 (3rd April 2021) - Blume, Arthur W.
ABSTRACT: Alcohol misuse has persisted in Indian country for generations. These disparities persist despite recent advances in services that often promote some combination of western-oriented conceptualizations of treatment with traditional healing and cultural practices. The intractability of alcohol and drug problems in many Indigenous communities suggests that current expressions of treatment are not sufficient to address substance misuse in these communities and effectively prepare clients for the post-treatment experiences of recovery. The focus of this paper is to generate hypotheses about what may be missing from the treatment today to improve treatment outcomes for Indigenous clients, and then propose ways for how treatment may be transformed from its current mostly western-oriented perspective to foundationally align with an Indigenous American worldview concerning well-being and health. Advancing treatment for American Indians and Alaska Natives includes consideration for how to address the consequences of colonialism that persist in ways that systematically harm the well-being and health of clients, how to align treatment models with Indigenous beliefs concerning an interdependent communalistic existence, and how to transform treatment to a holistic healing model that addresses alcohol and other substance misuse in the context of relationships.